Tarekat and Philanthropy: Reference from Wasiat 44 of the Tarekat Naqsyabandiyah Khalidiyah Babussalam - Ziaulhaq Hidayat (Al-Fikru: Jurnal Ilmiah, 2022)
Although it is always associated with spiritual worship, tariqa groups also have philanthropic teachings that increase their acceptability in society. This study aims to analyze the doctrine and practices of the philanthropy movement in the Tarekat Naqsybandiyah-Khalidiyah Babussalam in Kampung Besilam, North Sumatra. Doctrinal interpretation was used to analyze the philanthropic ground of thought in this group, while the analysis of its practice used sources from Wasiat 44 and field studies with interview and observation. This study found that the philanthropy movement of Tarekat Naqsybandiyah-Khalidiyah Babussalam comes from the doctrine taught by the founder of this tarekat, Tuan Guru ‘Abd al-Wahhab Rokan, who believes that support for the weak is an inseparable part of achieving spiritual perfection. This philanthropic movement continues from the first teacher to the present day of the Tuan Guru. The Tarekat Naqsybandiyah-Khalidiyah Babussalam philanthropy movement is realized in providing homes for widows, educational assistance, and compensation to orphans, as well as the empowerment of the poor and indigent with training in the manufacture of traditional medicines as part of the commodities around the Tarekat Naqsybandiyah-Khalidiyah Babussalam environment.